Latent profile analysis of perceived vulnerability among parents of children with febrile seizures - Cai, Yaxiu; Zhu, Haihong; Du, Yanping; Wang, Xiaohong; Chen, Cuie; Jiang, Yanping; Lan, Yuxiang (Frontiers in Pediatrics, 2025)
BackgroundCertain parents of children with febrile seizures have a high sense of perceived vulnerability, which may lead to overprotective behaviors. This study aimed to measure the latent profile types of perceived vulnerability in parents of children with febrile seizures and investigate the factors affecting these different profiles.MethodsA cross-sectional study was conducted from October 2023 to December 2024. Participants were surveyed using a general data questionnaire, the child vulnerability scale (CVS), parents’ perception of uncertainty scale (PPUS), and perceived social support scale (PSSS). Latent profile analysis (LPA) was conducted to identify different types of perceived vulnerability among parents of children with febrile seizures. The influencing factors for each profile were identified using univariate and multivariate logistic regression analysis.ResultsIn total, 400 participants were included in this study. The perceived vulnerability among parents of children with febrile seizures was divided into three latent profiles: “General Low Perceived Vulnerability Group” (37.9%), “Moderate Perceived Vulnerability Group” (32.8%), and “High Perceived Vulnerability Group” (29.3%). Multivariate analysis indicated that relationship with children, parents’ age, educational attainment, marital status, body temperature during febrile seizures, PPUS, and PSSS were the factors affecting perceived vulnerability in parents of children with febrile seizures.ConclusionThe perceived vulnerability in parents of children with febrile seizures exhibited significant heterogeneity. To minimize the perceived vulnerability, medical professionals should provide tailored mental health counseling and intervention based on vulnerability characteristics.